Legal rights : historical and philosophical perspectives - Sarat, Austin; Kearns, Thomas R. (Amherst series in law, jurisprudence, and social thought., 1997)
The idea of legal rights today enjoys virtually universal appeal, yet all too often the meaning and significance of rights are poorly understood. The purpose of this volume is to clarify the subject of legal rights by drawing on both historical and philosophical legal scholarship to bridge the gap between these two genres--a gap that has divorced abstract and normative treatments of rights from an understanding of their particular social and cultural contexts. Legal Rights: Historical and Philosophical Perspectives shows that the meaning and extent of rights has been dramatically expanded in.